KAJIAN MANAJEMEN TEKNOLOGI DALAM RANGKA PENINGKATAN DAYA SAING PERUSAHAAN (Studi Kasus: PD. XYZ, Produsen Kerupuk Udang) - Selliamanik, Irma; Sovania, Erina (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
Indonesia's national economic development is an important part of Indonesia's economic growth itself. Comparative advantage which is the basic capital must be supported by competitive advantage in seizing opportunities in the market. We know OVOP (one village one product) which is a regional program in the city of Ōita Prefecture, Japan which was implemented by Morihiko Hiramatsu in 1980, and Sakasakti (one district one core competency) which was initiated by Prof. Martani Husaini at the time of her inauguration as Professor, which is the basis for the competencies that the Indonesian government wants to encourage in order to improve the people's welfare equally, namely by utilizing the competencies possessed by each region. Crackers as a product resulting from the processing of natural resources are essentially an activity based on: (1). Advantages of natural resources (on-farm agribusiness), (2). A wide spectrum of activities from small scale businesses to export businesses, from traditional technology to advanced technology.